Microwave carbothermic reduction roasting of a low grade nickeliferous silicate laterite ore. (15th March 2016) - Forster, J.; Pickles, C.A.; Elliott, R.
Highlights: A thermodynamic model was employed to define the optimum experimental conditions. Highest nickel grade of 9.2% was achieved in argon, with a recovery of 89%. In argon, high recoveries were achieved at lower energy inputs than without argon. Enrichment ratios achieved were greater than those reported in the literature. Abstract: The known resources of nickel sulphide ores are quickly diminishing and in order to satisfy future nickel demands, nickel laterite deposits are being investigated as an alternative. Currently, expensive leaching and smelting processes are used to process the nickel laterite ores. The objective of the present research was to produce a high grade nickel concentrate via microwave carbothermic reduction roasting followed by magnetic separation. A thermodynamic model was developed for the roasting process in order to determine the optimum experimental conditions. The experimental variables investigated were: microwave energy and argon shrouding for the reduction tests and the magnetic field strength for the concentration stage. The behaviours of nickel and cobalt were studied in the reduction and magnetic separation processes. By optimizing the reducing and magnetic separation conditions, a high grade concentrate containing 9.2% nickel with a nickel recovery of 88.8% was achieved.